Estudo das propriedades ópticas e térmicas de superfícies quasicristalinas aplicadas em colheita de energia - Cavalcante, Rodrigo da Silva (2023)
Recent advances in the microelectronics industry have provided electronic devices with small dimensions and extremely low energy consumption. With regard to energy consumption, this has enabled the development of autonomous sources with low environmental impact. Aware of these transformations, Energy Harvesting is concerned with developing technology to harvest energy available in the surrounding environment of the system to be fed, thus, the useful life of this system/electronic device no longer depends on the useful life of your battery. In view of the above, the present study evaluates the selective and thermal potential of quasicrystalline alloys (QCs) based on AlCuFe, AlCrFe and AlCuCo as thin multilayer films sandwiched in dielectrics, varying their thickness in 10, 20, 50, 100 and 150 nm; and as a coating deposited on Al, Cu and stainless steel substrates. The influence of quasicrystalline coatings of 100, 200 and 300 μm on Al, Cu and steel reservoirs coupled in a Seebeck module, model GM200-71-14-16, from European Thermodynamics Limited, was verified. Such analyzes were carried out numerically by means of equations, considering the morphological aspects of the films and database available in the literature. The results showed that AlCuFe-based thin films with thicknesses of 10 and 20 nm developed absorbance above 85% and emittance below 15%, which is adequate selectivity for solar applications. The impacts of the coatings on the performance of the thermoelectric generator (TEG) were lower on Al and Cu substrates. The AlCrFe and AlCuCo alloys showed the best results such as higher voltage generated and better response time, when compared to the manufacturer's Datasheet. It was concluded in this study that quasicrystalline alloys are suitable for solar energy harvesting applications, either as multilayer thin films or as coatings in Seebeck modules.